Toxicidade aguda do sulfato de cobre e do extrato aquoso de folhas secas de nim para o caramujo (Pomacea canaliculata) - Venturini, Francine Perri [UNESP]; Da Cruz, Claudinei [UNESP]; Pitelli, Robinson Antonio [UNESP] (Universidade Estadual de Maringa, 2008)
Snails can become an environmental and economic problem, causing substantial losses. The objective of this work was to estimate the acute toxicity of copper sulfate pentahydrate (CuSO4.5H2O) and the aqueous extract of dried neem leaves on snails (P. canaliculata) under laboratory conditions. In order to estimate the lethal concentration 50% (LC (I)50;96h), snails were exposed to six increasing copper sulfate concentrations (0.0; 0.01; 0.03; 0.05; 0.07 and 0.1 mg L-1) and six increasing concentrations of aqueous extract of dried neem leaves 0.0; 100; 125; 150; 175 and 200 mL aqueous extract of dried neem leaves L-1 water, equivalent to (0.0; 1.18; 1.47; 1.77; 2.06 and 2.36 mg azadirachtin L -1), in triplicate and one control treatment in an entirely random delineation. Estimated LC (I)50;96h, of copper sulfate was 0.02 mg copper sulfate L-1, with a 0.01 mg L-1 lower limit and a 0.03 mg L-1 upper limit. Estimated lethal concentration 50% of the aqueous extract of dried neem leaves was 142.75 mL L-1, equivalent to 1.68 mg L-1 of azadirachtine, with a 130.89 mL L-1 (1.54 mg L-1) low limit and 155.69 mL L-1 (1.83 mg L -1) as the upper limit.
Acute toxicity of copper sulfate and aqueous extract of dried neem leaves on snails (Pomacea canaliculata)
Keywords: Copper; Lethal concentration; Mollusk; Natural pesticide; Azadirachta indica extract; azadirachtin; copper sulfate; Azadirachta indica; controlled study; LC 50; nonhuman; Pomacea canaliculata; snail; Gastropoda